2016
DOI: 10.1016/j.impact.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intratracheally instilled laser printer-emitted engineered nanoparticles in a mouse model: A case study of toxicological implications from nanomaterials released during consumer use

Abstract: Incorporation of engineered nanomaterials (ENMs) into toners used in laser printers has led to countless quality and performance improvements. However, the release of ENMs during printing (consumer use) has raised concerns about their potential adverse health effects. The aim of this study was to use “real world” printer-emitted particles (PEPs), rather than raw toner powder, and assess the pulmonary responses following exposure by intratracheal instillation. Nine-week old male Balb/c mice were exposed to vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 60 publications
3
27
0
Order By: Relevance
“…In our previous studies, it was found that human small airway epithelial cells, microvascular endothelial cells, macrophages, and lymphoblasts showed substantial changes in cell viability, production of reactive oxygen species, release of inflammatory cytokines and modifications to the DNA methylation machinery (1820). Animal experimental models have also confirmed the findings stated previously, including upregulation of neutrophils, macrophages and changes in the expression of genes that are involved in both the repair process from oxidative damage and the initiation of immune responses to foreign pathogens (21,22). Various epidemiological studies with detailed exposure characterization data have been done in photocopy centers.…”
Section: Introductionsupporting
confidence: 81%
“…In our previous studies, it was found that human small airway epithelial cells, microvascular endothelial cells, macrophages, and lymphoblasts showed substantial changes in cell viability, production of reactive oxygen species, release of inflammatory cytokines and modifications to the DNA methylation machinery (1820). Animal experimental models have also confirmed the findings stated previously, including upregulation of neutrophils, macrophages and changes in the expression of genes that are involved in both the repair process from oxidative damage and the initiation of immune responses to foreign pathogens (21,22). Various epidemiological studies with detailed exposure characterization data have been done in photocopy centers.…”
Section: Introductionsupporting
confidence: 81%
“…The Harvard compact cascade impactor (CCI) (Pirela et al 2016; Pal et al 2015; Pirela et al 2014; Demokritou et al 2004) was connected to e-cig mixing chamber for size-fractioned sampling. Particles were size fractionated and collected in three size fractions: PM 0.1 , PM 0.1–2.5 , PM 2.5–10 .…”
Section: Methodsmentioning
confidence: 99%
“…Nano-enabled thermoplastics or nanocomposites can contain nanofillers such as silica nanoparticles (Stojanović et al , 2013), clays (Fang et al , 2008), metal oxides (Perkgoz et al , 2011), carbon fibers (Al-Saleh et al , 2013) and carbon nanotubes (Sahoo et al , 2010) enabling extensive mechanical and electrical properties. Although, ENMs afford many useful properties, certain ENMs can cause adverse health effects such as cytotoxicity (DeLoid et al , 2016; DeLoid et al , 2014; Pirela et al , 2013; Pirela et al , 2014a), genotoxicity (Watson et al , 2013), epigenetic changes (Lu et al , 2016a; Lu et al , 2016b), and lung inflammation upon exposure (Borm et al , 2006; Konduru et al , 2014; Pirela, et al, 2013; Pirela et al , 2016). With this in mind, considerable concern over the hazards that may ensue due to the release of ENMs during consumer use and disposal of nano-enabled thermoplastics has created efforts to understand potential exposures across the life cycle of nano-enabled products (Bouillard et al , 2013; Grassian et al , 2016; Pirela et al , 2014b; Sisler et al , 2014; Wohlleben et al , 2011; Wohlleben and Neubauer, 2016).…”
Section: Introductionmentioning
confidence: 99%